2017
DOI: 10.5271/sjweh.3693
|View full text |Cite
|
Sign up to set email alerts
|

Is self-reported time spent sedentary and in physical activity differentially biased by age, gender, body mass index, and low-back pain?

Abstract: As one of the first of its kind, this study found that age and low-back pain, but not body mass index and gender, introduce differential bias in self-reported time spent sedentary and in physical activity. We therefore recommend that self-reported information on these behaviors should be used with due caution in clinical practice, in research, as well as when designing health promotion programs. Key terms: age; back pain; bias; blue-collar worker; body mass index; body mass index; exposure modelling; gender; l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 46 publications
1
28
0
Order By: Relevance
“…The bias related to self-reported occupational physical activity may be differential and may lead to an overestimation of the association between selfreported OPA and MSP. Gupta et al (Gupta et al 2018) reported that the extent of overestimating self-reported physical activity time depended on the level of musculoskeletal pain. Those with a high level of musculoskeletal pain overestimated their physical activity to a higher extent than those with a low level of musculoskeletal pain.…”
Section: Introductionmentioning
confidence: 99%
“…The bias related to self-reported occupational physical activity may be differential and may lead to an overestimation of the association between selfreported OPA and MSP. Gupta et al (Gupta et al 2018) reported that the extent of overestimating self-reported physical activity time depended on the level of musculoskeletal pain. Those with a high level of musculoskeletal pain overestimated their physical activity to a higher extent than those with a low level of musculoskeletal pain.…”
Section: Introductionmentioning
confidence: 99%
“…This method, which has been explained in more detail in the background section, is based on the notion that a log-ratio transformation of compositional variables will result in data expressed in an Euclidian space, which can then be analyzed using conventional statistical methods developed for non-constrained, normally distributed data (29). Thus, we expressed sitting, both self-reported and objectively measured, in terms of an isometric log-ratio (ILR), as used in several other studies applying CoDA to data on time spent in physical activities (18,29,32,34,46,47). The ILR expresses sitting in terms of the ratio of the percentages of time spent sitting to time spent nonsitting, ie, %sit/%non-sit, log-transformed and multiplied by 1/√2, ie, (noting that %non-sit equals 100 -%sit):…”
Section: Discussionmentioning
confidence: 99%
“…A number of additional factors that could likely influence workers' ability to assess sitting time (18) were added as candidate predictors to the calibration model based only on self-reported sitting. We obtained age (in years -calculated from the date of birth), gender (male/female) and smoking (yes/no).…”
Section: Self-reported Sitting Time and Other Predictorsmentioning
confidence: 99%
See 1 more Smart Citation
“…In particular, researchers have suggested that the PA paradox is merely a result of methodological limitations of existing studies (9). One such limitation lies in the measurements of PA, like the use of questionnaires that has been found to be imprecise and potentially biased (10,11). Besides this, existing prospective studies on the PA paradox have disregarded the compositional nature of time-use data like PA (12)(13)(14)(15).…”
mentioning
confidence: 99%